PENGECEKAN HANDPHONE DALAM PENGATURAN PENGGLEDAHAN BADAN OLEH PENYIDIK KEPOLISIAN - Rahmawati Sri Febriyani, (University (UIN) of Sunan Ampel Surabaya, 2023)
Search is one of the authorities of police investigators which is justified in law, in accordance with Article 33 Paragraph (1) of the Criminal Procedure Code. There are two types of searches, namely a house search and a body search or a person's clothes search.A body search is an act of investigators to examine the suspect's body and clothing to find objects that are allegedly hard on his body. However, cellphone inspection must be carried out according to the procedure.In Article 32 Paragraph 2 of the Chief of Police Regulation Number 8 of 2009 concerning Implementation of Human Rights Principles and Standards in the Implementation of Polri's Duties, the police are prohibited from carrying out excessive searches which result in disruption of the privacy rights of those being searched. This study aims to analyze the regulations related to body searches concerning cell phone checking carried out by police investigators and to find out the ideal and better body search procedures in the case of cell phone checking carried out by police investigators. This research applies normative juridical law research through statutory approach (statute approach) and conceptual approach (conceptual approach). The results of this study are that law enforcers, especially investigators, in carrying out body searches, especially when checking "forced" communication devices in the form of a mobile phone, cannot be arbitrary. current regulation.